English abilities and knowledge of adult leaners: A case study of student at the school of distance education, Universiti Sains Malaysia - Shahrier Pawanchik; Faiz Hilmi; Meor Azli; Issham Ismail (Proceedings of AICS - Social Sciences, 2013)
The decline in English language proficiency among students entering public universities isstill debatable. English may be taught from standard one through form five and form six ormatriculation level but the students’ proficiency is still very low. Looking at in microcosm,the majority of Malaysian students leave the school system with a poor grasp of Englishdespite having been exposed to the language for eleven or more years. Although both the‘intrinsic and extrinsic motivations’ have been given, these motivations have beenunsuccessful in reaching the greater majority. Employers especially from the private sectorhave voiced their concern on the low proficiency of these graduates. And the repercussion isemployers will look elsewhere for skilled workers instead of employing public institutions’graduates. Taking the cue from here, this research paper will focus on the abilities andknowledge of adult learners who are doing distance education programmes with the UniversitiSains Malaysia. These students are working either in the public or private sector. Findings ofthis research will provide information for curriculum developers at public institutions ofhigher learning to tailor their English courses towards meeting the students’ needs.